Linoleic acid, mitochondria, gut microbiome, and metabolic health: a mechanistic review - Joseph Mercola (Advances in Redox Research)
This hypothesis‐driven narrative review delineates the intricate mechanisms by which redox imbalance—encompassing both oxidative and reductive stresses—precipitates mitochondrial dysfunction in metabolic disorders. This review examines how excessive consumption of industrial seed oils rich in linoleic acid (LA) contributes to mitochondrial dysfunction, in part, by promoting peroxidation of lipids, including cardiolipin (CL), and altering mitochondrial bioenergetics. Such modifications destabilize electron transport chain (ETC) supercomplexes and elevate reactive oxygen species (ROS) generation, thereby compromising ATP production and overall mitochondrial efficiency. Additionally, we explore emerging evidence linking LA‐induced mitochondrial perturbations with gut dysbiosis, where impaired colonocyte metabolism disrupts the anaerobic niche critical for microbial balance, further propagating systemic inflammation. An integrative analysis of macronutrient quality and quantity suggests that strategic dietary modulation—particularly a marked reduction in LA intake—may restore mitochondrial redox homeostasis and improve metabolic health. By re-examining historical dietary trends alongside recent biochemical and clinical insights, this work underscores the critical role of mitochondrial membrane dynamics in metabolic pathophysiology and highlights targeted nutritional strategies to preserve mitochondrial integrity.